Archiwa uniwersytetów w Hiszpanii: organizacja, zasób i działalność - Jaśkowska, Zuzanna Maria (My University, 2015)
Praca składa się z 4 rozdziałów. Pierwszy z nich omawia prawne podstawy funkcjonowania hiszpańskich archiwów, w tym w szczególności archiwów uniwersyteckich. W rozprawie omówiono także proces adaptowania się placówek archiwalnych do państwowego ustawodawstwa. Kolejna część pracy skupia się na historii wybranych uniwersytetów i ich archiwów. Mowa o uczelniach w Salamance (powołana w roku 1218), Valladolid (powstała w końcu XIII wieku), Alcala de Henares, obecnie Complutense w Madrycie (1293) oraz w Saragossie (1542). W rozdziale trzecim przedstawiono najstarsze, najważniejsze i najciekawsze zasoby placówek wybranych uniwersytetów oraz dawne i współczesne pomoce ewidencyjno-informacyjne. Ostatnia część rozprawy dotyczy współczesnej organizacji archiwów: systemów zarządzania dokumentacją, zwanych w Hiszpanii systemami archiwalnymi, warunków lokalowych placówek oraz ich głównych zadań i funkcji. Ważny element rozdziału stanowi omówienie współpracy między pracownikami archiwów, jaka ma miejsce w ramach tzw. Dni Archiwów Uniwersyteckich.

Thesis contains 4 chapters. The first part is devoted to the legal basis of function of Spanish archives in general and - particularly - the archives of Spanish universities. The second part of doctoral thesis concentrates on history of higher education in the Iberian Peninsula and on history of chosen universities and its archives. The selected academies are University of Salamanca, founded in 1218, University of Valladolid (founded in late XIII century), University of Alcala de Henares, nowadays Complutense University in Madrid (1293) and University of Zaragoza (1542). The third chapter describes the oldest, the most important and the most numerous fonds of chosen archives. Besides the archival fonds, the chapter describes ancient and modern archival catalogues and inventories. The last part of doctoral thesis is devoted to current organization of archives of chosen universities. The chapter presents the archival systems introduced in academies composed of “active archives”, “semi-active archives” and “historical archives”. This part includes also analysis of the archival storages and offices, its sizes and equipment, the main tasks of archives ant the way of getting access to its fonds. The last part of the chapter concentrates on university archivist’s cooperation which take place during meetings called Jornadas de archivos universitarios organized since 1994.
The archives of universities in Spain: organization, fonds and activity
Wydział Historyczny: Instytut Historii
Keywords: archiwa uniwersyteckie; archives of universities; archiwistyka; archival science; Hiszpania; Spain